Interview with Christoph Wulf - Fredrik Lindstrand (Stockholm University Press, 2008)
In addition to the articles published in Designs for Learning, each issue will also include an interview with a person who is prominent within any of the fields that relate to the themes of the journal. The readers of this issue have already made acquaintance with professor Christoph Wulf through his article on mimetic learning. In the interview that follows we hope to give some further insights regarding interests and influences that form a background to his theoretical work. A further contextualisation of his article, so to speak.